Prevalence of and Factors Associated with Myopia in Inner Mongolia Medical Students in China, a cross-sectional study - Wang, Lan; Du, Maolin; Yi, He; Duan, Shengyun; Guo, Wenfang; Qin, Peng; Hao, Zhihui; Sun, Juan (BMC ophthalmology, 2017)
To further explore characteristics of myopia and changes in factors associated with myopia among students at Inner Mongolia Medical University. Two cross-sectional censuses were conducted in 2011 and 2013. Participants were medical students residing on campus in 2011 and 2013. Logistic regression analysis was performed to ascertain associations with basic information, genetic factors, environmental factors. The χ test was used to test for differences in prevalence between 2011 and 2013. Prevalence was calculated at various myopia occurrence times among different parental myopia statuses. A total of 11,138 students enrolled from 2007 to 2012 completed the questionnaire. The prevalence of myopia in 2011 and 2013 was 70.50% and 69.21%, respectively, no statistically significant difference existed between the two censuses (p = 0.12). Both censuses were completed by 1015 students. There were no differences among the various year of study in 2011 or 2013. Myopic prevalence increased with an increased number of myopic parents: the prevalence if both parents were myopic was over 90%, nearly 80% if one parent was myopic, and less than 70% with non-myopic parents (p < 0.001). Myopic occurrence ranked from earliest to latest was in kindergarten and primary school when both parents were myopic, in middle school when one parent was myopic, and in university when no parent was myopic. Students staying up late, using a computer more than 3 h per day, not performing eye exercises, using eye drops, and rubbing the eyes at high risk for myopia. Myopic status was stable during the university period. Genetic factors play a major role in myopia. Protective measures are useful for university students.